3 Challenges, 3 Errors, and 3 Solutions to Integrate Frontline Communities in Climate Change Policy and Research: Lessons From California - Fernandez-Bou, Angel Santiago; Ortiz-Partida, J. Pablo; Classen-Rodriguez, Leticia M.; Pells, Chantelise; Dobbin, Kristin B.; Espinoza, Vicky; Rodríguez-Flores, José Manuel; Thao, Chia; Hammond Wagner, Courtney R.; Fencl, Amanda; Flores-Landeros, Humberto; Maskey, Mahesh L.; et al. (Frontiers in Climate, 2021)
Frontline communities of California experience disproportionate social, economic, and environmental injustices, and climate change is exacerbating the root causes of inequity in those areas. Yet, climate adaptation and mitigation strategies often fail to meaningfully address the experience of frontline community stakeholders. Here, we present three challenges, three errors, and three solutions to better integrate frontline communities’ needs in climate change research and to create more impactful policies. We base our perspective on our collective firsthand experiences and on scholarship to bridge local knowledge with hydroclimatic research and policymaking. Unawareness of local priorities (Challenge 1) is a consequence of Ignoring local knowledge (Error 1) that can be, in part, resolved with Information exchange and expansion of community-based participatory research (Solution 1). Unequal access to natural resources (Challenge 2) is often due to Top-down decision making (Error 2), but Buffer zones for environmental protection, green areas, air quality, and water security can help achieve environmental justice (Solution 2). Unequal access to public services (Challenge 3) is a historical issue that persists because of System abuse and tokenism (Error 3), and it may be partially resolved with Multi-benefit projects to create socioeconomic and environmental opportunities within frontline communities that include positive externalities for other stakeholders and public service improvements (Solution 3). The path forward in climate change policy decision-making must be grounded in collaboration with frontline community members and practitioners trained in working with vulnerable stakeholders. Addressing co-occurring inequities exacerbated by climate change requires transdisciplinary efforts to identify technical, policy, and engineering solutions.